An Alternative Phase-Sensitive THz Imaging Technique for Art Conservation: History and New Developments at the ENEA Center of Frascati - Andrea Doria; Gian Piero Gallerano; Emilio Giovenale; Luca Senni; Manuel Greco; Marcello Picollo; Costanza Cucci; Kaori Fukunaga; Anne Cecile More (Applied Sciences, 2020)
In recent years, THz imaging techniques have been used in several fields of application. At the beginning of the century, the low availability of powerful THz sources was one of the limiting factors to the advancement of THz technology. At the ENEA center in Frascati, two Free Electron Lasers (FELs) operating in the THz spectral region were available at that time, making it possible to exploit all the features of THz imaging. In this paper, we will describe an alternative THz imaging technique, developed over 15 years of studies at the ENEA center of Frascati, and its application in the art conservation field, reporting the latest results of such studies on the optical properties of pigments in the GHz-THz region of the spectrum, on the possibility of detecting biological weeds under mosaic tiles and on the THz analysis of ancient leather wallpapers. This alternative technique was first developed in the framework of a bilateral collaboration between Japan and Italy, the THz-ARTE Project, which involved NICT (Tokyo), NNRICP (Nara), ENEA (Frascati) and IFAC-CNR (Florence). Most of the THz imaging techniques at that time were based on THz-Time Domain (THz-TD) devices. In the paper will be described how this alternative technique is able to measure the phase of the reflected radiation, thus providing information on the optical properties of the materials under study, such as mural paintings and mosaics. This makes it possible to detect the presence of hidden artworks, additional elements under paint layers, and dielectric materials. To describe the potential and the limits of this alternative imaging technique we will start from a description of the first THz imaging setup at the ENEA center of Frascati, based upon a THz Free Electron Laser. A description of the theoretical principle underlying this technique will be given. The first results in the field of art conservation are summarized, while the new results of a systematic study on the optical properties of pigments are reported and the realization of a portable THz imaging device, and its application “on site” for the analysis of frescoes are shown. The success of this prototype lead to the identification of different types of artworks as possible targets to be studied. New results about the ability of detecting water, and possibly the water content of biological weeds, under mosaic tiles are described, while new experimental measurements on Leather Wallpapers, both “in situ” and in a laboratory environment, are discussed later. A final analysis on the pro and the cons of this alternative imaging technique and on its possible utilization with the developed prototype is carried out together with the considerations on possible future developments and its potential use as an extension of other imaging techniques.